2023
DOI: 10.3389/fphar.2023.1081612
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-based loaded temozolomide nanoparticles conjugated by peptide-1 for glioblastoma chemotherapy and photothermal therapy

Abstract: Purpose: Nanoparticles (NPs) of the polydopamine (PDA)-based,loaded with temozolomide (TMZ) and conjugated with Pep-1 (Peptide-1) as a feasible nano-drug delivery system were constructed and utilized for chemotherapy (CT) and photothermal therapy (PTT) of glioblastoma (GBM).Method: PDA NPs were synthesized from dopamine (DA) hydrochloride and reacted with TMZ to obtain the PDA-TMZ NPs and then the PDA NPs and the PDA-TMZ NPs were conjugated and modified by Pep-1 to obtain the Pep-1@PDA NPs and Pep-1@PDA-TMZ NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In vivo studies demonstrated that this combination of targeted chemotherapy and PTT resulted in significantly improved antitumor efficacy compared to the use of chemotherapy alone. This suggests that the dual approach of combining PTT with chemotherapy could be more effective in treating GBM . In another study, self-assembled pH-responsive NPs loaded with modified camptothecin (CPT) and functionalized with ANG2 were also irradiated with an 808 nm laser.…”
Section: Beyond the Surface: Peptide Functionalization Strategies For...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies demonstrated that this combination of targeted chemotherapy and PTT resulted in significantly improved antitumor efficacy compared to the use of chemotherapy alone. This suggests that the dual approach of combining PTT with chemotherapy could be more effective in treating GBM . In another study, self-assembled pH-responsive NPs loaded with modified camptothecin (CPT) and functionalized with ANG2 were also irradiated with an 808 nm laser.…”
Section: Beyond the Surface: Peptide Functionalization Strategies For...mentioning
confidence: 99%
“…This suggests that the dual approach of combining PTT with chemotherapy could be more effective in treating GBM. 171 In another study, self-assembled pH-responsive NPs loaded with modified camptothecin (CPT) and functionalized with ANG2 were also irradiated with an 808 nm laser. The in vivo results in nude mice outlined a similar synergy between PTT and chemotherapy, with this combined approach exhibiting excellent tumor ablation and reduced side effects.…”
Section: Beyond the Surface: Peptide Functionalization Strategies For...mentioning
confidence: 99%